Valete vos viatores: travelling through latin inscriptions across the Roman Empire - Andreu Pintado, Javier, 1973-; Redentor, Armando; Alguacil Villanúa, Elena (Coimbra: Imprensa da Universidade de Coimbra, 2022)
Inscriptions were one of the trademarks of Romanization. Used as a real mass media, they covered almost all facets of Roman public and private life. Following common patterns, however, this habit of engraving inscriptions, the so-called “epigraphic habit”, took shape in different manifestations in each region, in each province, configuring diverse and attractive epigraphic cultures. This volume, the result of a Creative Europe project coordinated by the University of Navarra and with the participation of the University of Coimbra, the one at Bordeaux and La Sapienza in Roma and, also, of the Museo Nazionale Romano and different research centers in Portugal, France, Spain and Italy, reviews not only the functions of some of these inscriptions with new approaches to well-known repertoires but also the new tools that -from the rise of the Internet to the use of digital photogrammetry, from digital epigraphy to 3d epigraphy- are being implemented for their study, their understanding and, above all, the social dissemination of their values, builders, in large part, of European identity.
Incluye referencias bibliográficas.
Vegueta: Anuario de la Facultad de Geografía e Historia
Textos y resúmenes en portugués, inglés, francés, italiano y español.
Keywords: Inscripciones latinas; Epigrafía; Roma -- Historia -- 30 a.C.-476 d.C. (Imperio)